Evaluation of biofiltration materials for H2S removal - Mohammadi, Kamyab; Vaiškūnaitė, Rasa (International Conference “Environmental Engineering”, 2023)
H2S concentrations in Biogas are limited by environmental regulations. Hence, there are multiple purification methods as biological filtration are developed to meet the standards. In a typical biofiltration process, a bed of organic or inorganic porous materials is forced through a humid gaseous stream that contains the H2S pollutant, because it helps microbial growth and serves as the deck for the bioprocess, and is the most important part of a biofilter and the whole process of Biogas purification from H2S. An ideal packing medium ought to possess a number of characteristics, including a high mechanical resistance, the capacity to provide essential nutrients to a diverse microbial population, a large buffer capacity, a suitable moisture-holding capacity, a high specific area, and high porosity. The physicochemical properties and H2S removal efficiency of the biochar, compost, expanded schist, and waste of cellular concrete will be discussed and compared in this study.